Influence of local ionization on ionospheric densities in Titan's upper atmosphere. Issue 7 (20th July 2015) - Sagnières, Luc B. M.; Galand, Marina; Cui, Jun; Lavvas, Panayotis P.; Vigren, Erik; Vuitton, Véronique; Yelle, Roger V.; Wellbrock, Anne; Coates, Andrew J.
Abstract Titan has the most chemically complex ionosphere of the solar system. The main sources of ions on the dayside are ionization by EUV solar radiation and on the nightside include ionization by precipitated electrons from Saturn's magnetosphere and transport of ions from the dayside, but many questions remain open. How well do models predict local ionization rates? How strongly do the ionization processes drive the ionospheric densities locally? To address these questions, we have carried out an analysis of ion densities from the Ion and Neutral Mass Spectrometer (INMS) from 16 close flybys of Titan's upper atmosphere. Using a simple chemical model applied to the INMS data set, we have calculated the ion production rates and local ionization frequencies associated with primary ions <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fzrhmwk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />N2+</alternatives> and <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fzrhmx4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CH4+</alternatives>. We find that on the dayside the solar energy deposition model overestimates the INMS‐derived <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fzrhmzp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />N2+</alternatives> production rates by a factor of 2. On the nightside, however, the model driven by suprathermal electron intensities from the Cassini Plasma Spectrometer Electron Spectrometer sometimes agrees and other times underestimates the INMS‐derived <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fzrhn0r" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />N2+</alternatives> production rates by a factor of up to 2–3. We find that below 1200 km, all ion number densities correlate with the local ionization frequency, although the correlation is significantly stronger for short‐lived ions than long‐lived ions. Furthermore, we find that, for a given N2 local ionization frequency, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2fzrhn19" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />CH5+</alternatives> has higher densities on the dayside than on the nightside. We explain that this is due to CH4 being more efficiently ionized by solar photons than by magnetospheric electrons for a given amount of N2 ionization.